2016
DOI: 10.3390/ma9060447
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Materials for Water Purification

Abstract: Water scarcity issues associated with inadequate access to clean water and sanitation is a ubiquitous problem occurring globally. Addressing future challenges will require a combination of new technological development in water purification and environmental remediation technology with suitable conservation policies. In this scenario, new bioinspired materials will play a pivotal role in the development of more efficient and environmentally friendly solutions. The role of amphiphilic self-assembly on the fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Nature offers hierarchical architectures with multilevel light scattering, high electron-diffusion length, open and accessible porosity, high surface-to-volume ratios, and high light absorption independent from incident light angle, among other important characteristics for photochemistry. It is well known that human-made materials have been unable to compete with nature in general [39][40][41][42]. It is, therefore, a smart strategy to synthesize bioinspired materials to develop more efficient and competitive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nature offers hierarchical architectures with multilevel light scattering, high electron-diffusion length, open and accessible porosity, high surface-to-volume ratios, and high light absorption independent from incident light angle, among other important characteristics for photochemistry. It is well known that human-made materials have been unable to compete with nature in general [39][40][41][42]. It is, therefore, a smart strategy to synthesize bioinspired materials to develop more efficient and competitive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Design bioinspired fibres for water collection (inspired by spider silk) [20][21][22] Nanomaterials or bioinspired materials for water purification and decontamination [7,13,[23][24][25] Membranes and biomembranes to treat and re-use water from industry, waste streams and groundwaters [16,[26][27][28] Liquid-liquid extraction procedures using ionic liquids to decontaminate water.…”
Section: Technology-objective Referencesmentioning
confidence: 99%
“…Besides, those authors suggested to abandon subjective quantifications of human environments and to use the measurement of water scarcity to inform participatory decision-making processes that explore a wide range of options for addressing freshwater storage requirements beyond dams that include use of renewable groundwater, soil water and trading in virtual water [8,12]. Consequently, addressing future challenges will require a combination of new technological development in water storage/purification/desalinization and environmental remediation technology with suitable conservation policies [13][14][15][16]. Although desalinization remains one of the most expensive ways to produce potable water, water scarcity also forces populations to find new sources of drinking water; therefore, scientists are developing innovations that may soon make desalination a reasonable option for many more communities [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Thousands of industrial and agriculture chemical compounds are being discharged into freshwater system without effective treatment [ 1 , 2 ]. Most toxic pollutants featured with stubborn conjugated structure appear at trace concentrations such as dyes, antibiotics and pesticides, but many of them cause pathogenic concerns due to their chemical durability and bioaccumulation [ 3 , 4 , 5 ]. The abundance of background inorganic or/and organic constituents make them difficult to deal with [ 1 ].…”
Section: Introductionmentioning
confidence: 99%